A pH‐Switchable Triple Hydrogen‐Bonding Motif. Issue 1 (8th January 2020) - Coubrough, Heather M.; Balonova, Barbora; Pask, Christopher M.; Blight, Barry A.; Wilson, Andrew J.
Abstract: A stimuli responsive linear hydrogen bonding motif, capable of in situ protonation and deprotonation, has been investigated. The interactions of the responsive hydrogen bonding motif with complementary partners were examined through a series of 1 H NMR experiments, revealing that the recognition preference of the responsive hydrogen bonding motif in a mixture can be switched between two states. Abstract : A pH responsive linear triple hydrogen bonding motif capable of protonation and deprotonation, has been investigated. A series of 1 H NMR experiments, revealed that the preference of this responsive hydrogen bonding motif in a mixture of hydrogen bonding motifs, can be switched between two self‐sorted states.